(untitled) (Journal of Pharmaceutical Negative Results, 2022)
One of the treatment methods in the field of dental prostheses is placing veneers on severely damaged root treated teeth. The holding power of the veneer is one of the important success factors in such treatments, especially when the teeth have short crowns. One of the factors that can affect the strength of the coating on such teeth is cement. In this interventional laboratory study, silver cast alloy coatings were made on 14 identical dies made of Core Max II, and the dies were randomly divided into 3 groups of 10, and in each group, the coatings were made on the die made of Core Max II was cemented with one of zinc phosphate cement (Harward), glass ionomer (Fugi GC) and Panavia (Kurary) F. Based on quantitative analysis, there was a significant difference between three glass ionomer cements, zinc phosphate and Panavia F in terms of setting. An ideal cement should have good mechanical properties to resist functional forces, adhere well to the underlying surface of the coating, and have high stress tolerance. In addition to cement, the type of blind building material and the physical and chemical relationship between adhesive cement and blind building material are also very important.